Marketing Aspect of Banking Competition - Nieizviestna Olena V. (Problemi Ekonomiki, 2015)
The aim of the article is to study the need for application of marketing tools in order to improve competitiveness and competitive advantages of banks. By analyzing, systematizing and summarizing the scientific works of many scientists, the relationship between the competitiveness of the commercial bank and its share in the banking market has been discovered. In the process of studying the integration of the strategy of maximizing customer satisfaction in the practice of strategic competition in the banking market there was presented the author’s position regarding the need to take into account the structure of the customer loyalty, as it is it that helps to properly distribute the bank’s marketing efforts. It has been proved that the technology of bank marketing should not only include the systems of identifying customer needs, creation of new financial products, but also contribute to the formation of the multi-factor strategic model of competitive strategy of the bank competitive development. It has been proposed to use the SWOT-analysis in order to effectively manage the bank’s competitiveness.